Introduction. Thematic dossier of GT-1 of the Space and Economy Colloquium. “Financial dominance, platform capitalism, and productive restructuring” - Rufino, Beatriz; Tozi, Fábio; Pessanha, Roberto Moraes (Geografares, 2026)
The dossier brings together the articles presented in the homonymous Working Group that was part of the V International Space and Economy Colloquium, and it features research that unveils the voracity of the association between financialization and platformization in the different domains of social life and the productive sphere. The papers present analyses of various contemporary manifestations of the territory’s digitalization process, which began a few decades ago. By presenting an overview of emerging themes, we hope that this set of texts can help other researchers advance in their investigations, with rigorous theoretical-conceptual debates and creative methodologies. We hope that the results shared here can broaden the dialogues of researchers dedicated to the theme, with the presented works opening paths for new debates and perspectives on capitalist restructuring in its multiple and contradictory processes.